Urban Sustainability Transitions Towards Asbestos-Free Municipalities - Macher, Gergely Zoltán (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The phase-out of asbestos in urban environments represents a complex challenge across European municipalities. Despite European Union targets to achieve asbestos-free cities, implementation remains uneven because municipalities face fragmented regulations, differing inspection and disclosure requirements, limited funding, technical constraints, and variable public awareness. The paper identifies key barriers, including regulatory heterogeneity, inadequate disposal infrastructure, and financing gaps, as well as enabling factors such as harmonized policies, innovative treatment technologies, capacity-building programs, and community engagement. Based on these insights, a typology of municipal transition pathways is developed, including compliance-driven, retrofit-integrated, innovation-led, community-driven, and market-based approaches. The findings also underline equity considerations, emphasizing the need to prevent disadvantaged communities from remaining disproportionately exposed to asbestos hazards. By framing asbestos removal as a material legacy transition within broader urban sustainability transitions, the paper contributes both to theoretical understanding of socio-technical and ecosystem dynamics and to practical guidance for policymakers and urban planners.